Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3892/ol.2019.10005
|View full text |Cite
|
Sign up to set email alerts
|

Association of estradiol and HPV/HPV16 infection with the occurrence of cervical squamous cell carcinoma

Abstract: The associations between human papillomavirus (HPV) infection or hormonal exposure and cervical cancer risk are well established. However, to the best of our knowledge, the association between high endogenous estradiol levels in conjunction with HPV/HPV16 infection and the risk of cervical squamous cell carcinoma remains unknown. To investigate this, the current study conducted a matched case-control study in Shanxi Province, China, in which clinical samples were obtained from 74 females with newly diagnosed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
(34 reference statements)
1
9
0
1
Order By: Relevance
“…Epidemiological studies have shown that oral contraceptives and multiple pregnancies are risk factors for cervical cancer [24]. Further, HPV-positive women with high estradiol levels had higher risk of cervical cancer than women who were only either HPV-positive or exhibited high levels of estradiol [25]. These results confirm the additive effect of estradiol and HPV infection found in experimental studies.…”
Section: Discussionsupporting
confidence: 75%
“…Epidemiological studies have shown that oral contraceptives and multiple pregnancies are risk factors for cervical cancer [24]. Further, HPV-positive women with high estradiol levels had higher risk of cervical cancer than women who were only either HPV-positive or exhibited high levels of estradiol [25]. These results confirm the additive effect of estradiol and HPV infection found in experimental studies.…”
Section: Discussionsupporting
confidence: 75%
“…One possible explanation for the enhanced susceptibility of the cervix to persistent infection compared to the anus is the role of endogenous estrogen. Estrogen has been shown to play a key role in potentiating the development of cervical cancer, and clinical evidence suggests that higher estrogen levels are associated with increased persistence of high-risk HPVs ( 54 , 55 ). Furthermore, we have shown that MmuPV1 infection persists in 100% of mice treated with exogenous estrogen and that estrogen-treated mice developed more severe disease ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that HPV infection has a significant association with the occurrence and progression of CSCC ( Ding et al, 2019 ). Therefore, we separately analyzed the ImmuneScore, StromalScore and ESTIMATEScore distribution among CSCC patients with or without HPV infection.…”
Section: Resultsmentioning
confidence: 99%